2011
DOI: 10.1074/jbc.m110.177790
|View full text |Cite
|
Sign up to set email alerts
|

Activation of D1/D5 Dopamine Receptors Protects Neurons from Synapse Dysfunction Induced by Amyloid-β Oligomers

Abstract: Soluble oligomers of the amyloid-␤ peptide (A␤Os) accumulate in the brains of Alzheimer disease (AD) patients and are implicated in synapse failure and early memory loss in AD. A␤Os have been shown to impact synapse function by inhibiting long term potentiation, facilitating the induction of long term depression and inducing internalization of both AMPA and NMDA glutamate receptors, critical players in plasticity mechanisms. Because activation of dopamine D1/D5 receptors plays important roles in memory circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 61 publications
4
60
1
Order By: Relevance
“…It has been reported that selective activation of D1/D5 receptors could protect synapses in AD. An association has also been observed between D2 receptor availability in the right hippocampus and cognitive performance in AD [13,14] . The central nervous system (CNS) pharmacokinetics (PK) of a drug are important determinants in the time course and intensity of its effects, if the action compartment of which is in CNS.…”
Section: Introductionmentioning
confidence: 79%
“…It has been reported that selective activation of D1/D5 receptors could protect synapses in AD. An association has also been observed between D2 receptor availability in the right hippocampus and cognitive performance in AD [13,14] . The central nervous system (CNS) pharmacokinetics (PK) of a drug are important determinants in the time course and intensity of its effects, if the action compartment of which is in CNS.…”
Section: Introductionmentioning
confidence: 79%
“…Accordingly, it was recently found that activation of D1 receptors with a selective agonist in hippocampal slices protects synapses from deleterious effects on LTP and prevents the decrease of surface NMDA and AMPA receptors caused by Ab exogenous administration in hippocampal neurons (Jurgensen et al 2010). Another possible basis of the DA dysfunction during the acquisition stage is related to the influence of cholinergic transmission over neurotransmitters release, including DA.…”
Section: Discussionmentioning
confidence: 99%
“…Besides IRs, other proteins important for synaptic plasticity, including NMDA- (47,48) and AMPA-type glutamate receptors (49), are removed from the cell surface when neurons are exposed to oligomers, indicating a broad impact on synapses. Oligomer actions are thought to underlie other aspects of brain dysfunction in AD, activating signaling pathways that lead to abnormal tau phosphorylation (50)(51)(52) and oxidative stress (53)(54)(55), both hallmarks of AD pathology.…”
Section: Amyloid-β Oligomers: Synaptotoxins That Build Up In the Ad Bmentioning
confidence: 99%